Low-temperature chemical synthesis of intermetallic TiFe nanoparticles for hydrogen absorption. (23rd June 2021) - Kobayashi, Yasukazu; Yamaoka, Shohei; Yamaguchi, Shunta; Hanada, Nobuko; Tada, Shohei; Kikuchi, Ryuji
Abstract: Nanosizing of TiFe hydrogen storage alloy is conducted to facilitate its activation. Here, pure intermetallic TiFe nanoparticles (45 nm) were prepared using chemical reduction of oxide precursors at 600 °C, which is the lowest temperature ever used in chemical synthesis. This was achieved using a strong reducing agent (CaH2 ) in a molten LiCl. When used for hydrogen absorption, the obtained nanoparticles surprisingly exhibited almost no hydrogen absorption. The results demonstrated that TiFe nanoparticles are more difficult to activate than the bulk powder because the oxidized surface layers of the nanoparticles become stabilized, which prevents the morphological change necessary for their activation. Highlights: Chemical synthesis of intermetallic TiFe from oxide precursors at 600 °C. Preparation of highly pure intermetallic TiFe nanoparticles (45 nm). A negative effect of the size of TiFe nanoparticles on the hydrogen absorption.